Stabilization of different redox levels of a tridentate benzoxazole amidophenoxide ligand when bound to Co(iii) or V(v) 1. Issue 35 (20th August 2019) - Safaei, Elham; Balaghi, S. Esmael; Chiang, Linus; Clarke, Ryan M.; Martelino, Diego; Webb, Michael I.; Wong, Edwin W. Y.; Savard, Didier; Walsby, Charles J.; Storr, Tim
Abstract : The electronic structure of Co and V complexes of a tridentate benzoxazole-containing aminophenol ligandNNO H2 were characterized by both experimental and theoretical methods. Abstract : A tridentate benzoxazole-containing aminophenol ligandNNO H2 was coordinated to Co and V metal centers and the electronic structure of the resultant complexes characterized by both experimental and theoretical methods. The solid state structure of the Co complex exhibits a distorted octahedral geometry with two tridentate ligands bound in meridional fashion, and coordination-sphere bond lengths consistent with a Co(iii ) oxidation state. EPR and magnetic data support a S = 1/2 ground state, and a formal electronic description of Co(iii )(NNO AP )(NNO ISQ ) whereNNO AP corresponds to an amidophenoxide andNNO ISQ to the iminosemiquinone redox level. However, the metrical parameters are similar for both ligands in the solid state, and DFT calculations support delocalization of the ligand radical over both ligands, affording an intermediate ligand redox level Co(iii )(NNO 1.5− )(NNO 1.5− ). The vanadyl complex exhibits a distorted octahedral geometry in the solid state consistent with a V(v ) metal center and amidophenoxide (NNO AP ), acetylacetonate and oxo ligands. The ligand metrical parameters are consistent with significant amidophenoxide to V(v ) π donation. Overall, our results highlight the roles of electron transfer, delocalization, and π bonding in the metal complexes under study, and thus the complexity in assignment of the electronic structure in these systems.